2010
DOI: 10.1007/s11199-010-9775-5
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Social Dominance Orientation: The Role of Cognitive Complexity

Abstract: The present research examined the invariance hypothesis, which predicts lower levels of social dominance orientation (SDO) for women compared to men even when accounting for other factors. Previous research shows that gender linked variables mediate the gender difference in SDO. In two studies using undergraduates in the northeastern U.S., we tested mediation by cognitive complexity, a variable linked to social status but not to gender. Study 1 (n=117) found that women had higher levels of attributional comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Women are supposedly easy going due to gender roles. Women also have had scored higher than men on the attributional complexity scale supporting previous research (Foels and Reid, 2010;Tam, Au and Leung, 2008). Women prefer complex explanations to the incidents happening around them.…”
Section: Conclusion Discussion and Suggestionssupporting
confidence: 81%
“…Women are supposedly easy going due to gender roles. Women also have had scored higher than men on the attributional complexity scale supporting previous research (Foels and Reid, 2010;Tam, Au and Leung, 2008). Women prefer complex explanations to the incidents happening around them.…”
Section: Conclusion Discussion and Suggestionssupporting
confidence: 81%
“…Further, there are cognitive gender differences that support our supposition, especially in how men and women vary in processing information about people. women have higher attributional complexity (the degree to which an individual considers multiple kinds of information regarding someone in deep processing for social judgements) than men do [ 49 , 50 ]; concerning information processing, women (more than men) are concerned of others, have a lower threshold for message elaboration and extensively use message cues, all indicating they generally process more messages from others and rely less on heuristics to decide the value of a message [ 51 57 ]; …”
Section: Introductionmentioning
confidence: 99%
“…women have higher attributional complexity (the degree to which an individual considers multiple kinds of information regarding someone in deep processing for social judgements) than men do [ 49 , 50 ];…”
Section: Introductionmentioning
confidence: 99%
“…Within psychological measurement practice, this kind of equivalence in the functioning of instruments is known as invariance (Byrne, Shavelson, & Muthén, 1989); establishing invariance is essential to make meaningful comparisons across groups (Rusticus & Hubley, 2006). Several studies have shown that gender role socialization can exist at different levels (e.g., Foels & Reid, 2010;Rusticus & Hubley, 2006); women and men can, for example, differ not only in how they relate to or attribute importance to perceive a certain issue (such as environmental problems) but also in how they conceptualize that issue. Gender differences might be present at the construct level as well as at the level of item interpretation or functioning.…”
mentioning
confidence: 99%